PRIMA 2013: Principles and Practice of Multi-Agent Systems 16th International Conference, Dunedin, New Zealand, December 1-6, 2013. Proceedings - Boella, Guido; Elkind, Edith; Savarimuthu, Bastin Tony Roy; Dignum, Frank; Purvis, Martin K. (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the refereed proceedings of the 16th International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2013, held in Dunedin, New Zealand, in December 2013. The conference was co-located with the 26th Australasian Artificial International Conference, AI 2013. The 24 revised full papers presented together with 18 short papers and 2 invited papers were carefully reviewed and selected from 81 submissions. The papers are organized in topical sections on foundations of agents and multi-agent systems; agent and multi-agent system architectures; agent-oriented software engineering; agent-based modelling and simulation; cooperation/collaboration, coordination/communication; hybrid technologies, application domains; and applications.